Management of acute periprosthetic joint infection of the knee – Algorithms for the on call surgeon. Issue 2 (April 2017) - Petretta, Robert; Phillips, Jonathan; Toms, Andrew
Abstract: Periprosthetic joint infection (PJI) remains a serious complication following a total knee replacement. Infections rates following arthroplasty range from 0.5% to 3%. The acutely infected knee replacement often presents to the on call Orthopaedic Surgeon who can often lack the expertise or resources for the definitive management. However, obtaining an early and accurate diagnosis and potentially performing an early treatment such as irrigation and debridement may be required by the on call surgeon. Management of these patients should include a team of specialists including Medical or Intensive Care, and Infectious Disease. Management of PJI is expensive, complicated and has a high morbidity. These patients should have their definitive care by specialist multidisciplinary teams on a regional basis.